Efficiency and reduction cost of carbon emissions in China: a non-radial directional distance function method. (1st February 2016) - Wang, Sufeng; Chu, Chu; Chen, Guozhong; Peng, Zhanglin; Li, Fangyi
Abstract: The assessment of carbon emission performance is crucial to formulate environmental policies. Few studies have systematically examined environmental efficiency from the perspective of regional temporal–spatial differences and evolution laws. In this paper, we evaluate the carbon emission efficiency and reduction cost in 30 provinces of mainland China from 1996 to 2012 using the non-radial directional distance function method. Three primary carbon emission zones, i.e., the steep-slope zone, flat zone, and plateau zone are classified and compared comprehensively in terms of emission performance (measured by Malmquist index), abatement cost (measured by shadow price), and potential emissions (measured by the growth rates of emissions and economic outputs). Results show that, carbon emission efficiency varies greatly among zones and is closely related to regional economic development. The shadow price for each zone and the whole country between 1996 and 2012 presents a remarkable regularity that it kept increasing at first and decreased afterwards, reaching the maximum value at the year 2000. Furthermore, the carbon emissions in three zones exhibit significant differences. Meanwhile, similarities exist within each zone, indicating that environmental policies designed for different zones and emissions trading across zones are rather necessary and feasible. The empirical estimations from this study provide an analytical basis for the implementation of carbon emission regulations and would facilitate a balanced and sustainable development of China's environment and economy. Graphical abstract: Highlights: We estimate Malmquist environmental index based on a non-radial DDF method. We measure shadow price of carbon emissions to reflect reduction costs. The nation can be divided into three emission zones: steep-slope, flat and plateau zone. Carbon emission performances varied greatly among provinces. Shadow price of China kept increasing before 2000 and then declined afterwards.